Diplomasi Belanda dan Indonesia dalam Sengketa Irian Barat, 1949-1950: Sebuah Kajian Historis - Ahmed, Siswanto (Jurnal Penelitian Politik, 2016)
This article would like to understand the history of diplomacy of Dutch and Indonesia in West Papua dispute in 1949 to 1950. According to historical documents, West Papua dispute has begun since Round Table Conference in 1949. In that Conference, the delegation of Dutch and Indonesian agreed to renegotiate West Papua problem one year after the Conference. In April 1950, Dutch and Indonesia negotiated the problem in Jakarta, but both countries could not produce a significant commitment. In December 1950 Dutch and Indonesia held a Special Conference in Hague in order to solve the problem, but once again they are failed. The peace proposal which is introduced by both countries is so contradicted one another. At last, West Papua dispute could not be negotiated successfully because Dutch did not have serious intention to transfer West Papua to Indonesia.